Bericht über Agrargeographische Untersuchungen in der Gombe Division, Bauchi Province, Nord-Nigeria - Fricke, Werner (ERDKUNDE, 1965)
The aim of the field work in 1961 was to make a general survey of the influence of historical factors on the structural patterns of agriculture and settlement in the savanna zone of West Africa, It is a well known fact since C. D. Forde's pioneering work that Nigerian economy is regionally differentiated by ethnic-historical facts i.e. Hausa economy, Middle Belt economy, and Pastoral economy. All of these types are to be found in Gombe Division (approx. 6.350 square miles & 500.000 inhabitants). There quarters of that area and population form the Gombe Emirate ruled by descendents of Fulani conquerors, while the remaining districts constitute the Independent Federation of Tangale Waja. This Federation unites a number of small tribes which in a hilly country withstood the onslaughts of the Fulani cavalry till the pacification and therefore still show all the symptoms of the so called Middle Belt economy. Despite the existing uniformity of their sociology and economy some tribes differ in the lay-out of the compounds, terraced hill-farms, and farming methods. Consequently, as they have only recently settled on the plains, they show differing adaptability to the change of natural and social conditions. In the plains of the Emirate some Fulani settlements of different age have been studied likewise. The regular lay out of some older villages shows similarities to temporary camps of nomadic Fulani. Mostly the upper classes of the settled Fulani still keep cattle; 70% of the 145.000 head of taxed cattle in Gombe Division are owned by them. The nomadic Fulani cattle breeder migrate seasonally and regularly depending on climate and possibilities of pasturing; this again is influenced by the rapid spread and increase of farmland especially in the centre of Gombe Division on black cotton soils. Since 1952 this district has become an important cotton growing area which in 1959/60 produced 15% of the Nigerian output. This development may partly be due to the introduction of the plough by the government.